EXTENT OF HOST COMMUNITY INVOLVEMENT IN FUND MOBILIZATION FOR EFFECTIVE ADMINISTRATION OF SECONDARY SCHOOLS IN DELTA STATE (Journal of Association of Educational Management and Policy Practitioners, 2024)
This study examined the extent of host community involvement in fund mobilization for effective administration of secondary schools in Delta State. Four research questions were raised to guide the study and a descriptive survey research design was adopted in the study. Population of this study comprised 13,760 staff involving 474 principals and 13,286 teachers from 474 public secondary schools within the 25 LGAs in Delta State. Sample size for the study constituted a total of 558 respondents which consisted of 133 principals and 425 teachers from 133 public secondary schools within 13 LGAs in Delta State selected at 50% and 5% respectively using the multistage sampling procedure involving the proportionate and purposive sampling techniques. A 35-item questionnaire personally constructed by the researchers, titled: “Host Community Involvement in Fund Mobilization for Effective Administration Questionnaire (HCIFMEAQ)” was used for data collection. Both validity and reliability of the research instrument was established in the study. Data collated were analyzed using mean statistics rated at 2.50 and standard deviation statistics for answering the research questions. Findings of the study revealed among others that, host community involvement in fund mobilization for effective administration of secondary schools in Delta State was to a low extent. That is, host community involvement in fund mobilization in areas of effective instructional leadership administration, school plant (facilities) administration, teacher administration and student administration in secondary schools in Delta State were all to a low extent. From the findings of this study, recommendations were proffered and among them included that, the Delta State Government together with the Post Primary Education Board (PPEB) should constantly organize leadership training programmes that will strengthen ties between schools and their immediate host communities for their active involvement and contributions in fund mobilization for effective instructional leadership administration in secondary schools.